Fungal communities in soils under global change - Baldrian, P; Bell-Dereske, L; Lepinay, C; Větrovský, T; Kohout, P (Studies in mycology, 2022)
Soil fungi play indispensable roles in all ecosystems including the recycling of organic matter and interactions with plants, both as symbionts and pathogens. Past observations and experimental manipulations indicate that projected global change effects, including the increase of CO2 concentration, temperature, change of precipitation and nitrogen (N) deposition, affect fungal species and communities in soils. Although the observed effects depend on the size and duration of change and reflect local conditions, increased N deposition seems to have the most profound effect on fungal communities. The plant-mutualistic fungal guilds - ectomycorrhizal fungi and arbuscular mycorrhizal fungi - appear to be especially responsive to global change factors with N deposition and warming seemingly having the strongest adverse effects. While global change effects on fungal biodiversity seem to be limited, multiple studies demonstrate increases in abundance and dispersal of plant pathogenic fungi. Additionally, ecosystems weakened by global change-induced phenomena, such as drought, are more vulnerable to pathogen outbreaks. The shift from mutualistic fungi to plant pathogens is likely the largest potential threat for the future functioning of natural and managed ecosystems. However, our ability to predict global change effects on fungi is still insufficient and requires further experimental work and long-term observations. Citation: Baldrian P, Bell-Dereske L, Lepinay C, Větrovský T, Kohout P (2022). Fungal communities in soils under global change. Studies in Mycology 103: 1-24. doi: 10.3114/sim.2022.103.01.
Keywords: global change; nitrogen; warming; deposition; drought; elevated CO2; mycorrhiza